What Effect Does Transition Have on Health and Well‐Being in Young People with Intellectual Disabilities? A Systematic Review. Issue 5 (24th August 2016) - Young‐Southward, Genevieve; Philo, Christopher; Cooper, Sally‐Ann
Abstract : Background: Transition to adulthood might be a risk period for poor health in people with intellectual disabilities. However, the present authors could find no synthesis of evidence on health and well‐being outcomes during transition in this population. This review aimed to answer this question. Method: PRISMA/MOOSE guidelines were followed. Search terms were defined, electronic searches of six databases were conducted, reference lists and key journals were reviewed, and grey literature was searched. Papers were selected based on clear inclusion criteria. Data were extracted from the selected papers, and their quality was systematically reviewed. The review was prospectively registered on PROSPERO: CRD42015016905. Results: A total of 15 985 articles were extracted; of these, 17 met the inclusion criteria. The results of these articles were mixed but suggested the presence of some health and well‐being issues in this population during transition to adulthood, including obesity and sexual health issues. Conclusion: This review reveals a gap in the literature on transition and health and points to the need for future work in this area.